Plasma Concentrations of Digoxin after Oral Administration in the Fasting and Postprandial State. Issue 5745 (13th February 1971) - White, R. J.; Chamberlain, D. A.; Howard, M.; Smith, T. W.
Abstract : After the oral administration of 0·5 mg of digoxin in tablet form to fasting subjects peak plasma levels were reached in 30 to 60 minutes. Levels then fell to reach a plateau at six to eight hours. When the same dose was given after food the peak plasma concentrations were significantly lower, but the concentrations reached in samples obtained from two to eight hours after the dose did not differ appreciably from corresponding samples obtained in the fasting experiments. In a four-week cross-over study of 21 patients on maintenance therapy, digoxin taken regularly in the fasting state produced plasma concentrations similar to those obtained when the drug was taken after meals. The rapid appearance of digoxin in the blood suggests that the oral route of administration is adequate for most patients who require rapid digitalization, and the timing of maintenance dosage in relation to meals is unimportant.